High‐Density Display of Protein Ligands on Self‐Assembled Capsules via Noncovalent Fluorous Interactions. Issue 1 (17th November 2014) - Harano, Koji; Yamada, Junya; Mizuno, Shinichiro; Nakamura, Eiichi
Abstract Ligand display on self‐assembled nanostructures is an important tool in generating bioactive materials. Here, we demonstrate the display of sugar and biotin molecules on sub‐100 nm‐sized capsules with a high surface coverage, which was achieved by the use of noncovalent fluorous interactions between a fluorous‐tagged ligand molecule and a fullerene vesicle covered with fluorous chains. Even after the high‐density ligand display and protein binding, the vesicle stably maintains its spherical structure because the fluorous binding of the sugar does not affect the structural integrity of the vesicle that originates from strong fullerene–fullerene interactions.